1996
DOI: 10.2169/internalmedicine.35.987
|View full text |Cite
|
Sign up to set email alerts
|

Evans' Syndrome Associated with Graves' Disease.

Abstract: A 36-year-old womanwho had had Graves' disease for 6 years was admitted with severe thrombocytopenia. Evans' syndrome was diagnosed. The patient's family history showed multiple cases ofGraves' disease but no cases ofEvans' syndrome. Both conditions in this patient improved with corticosteroid and thiamazole therapy. Several autoimmuneantibodies were found, but a commonautoimmunemechanism was not clearly shown. Although the combination of Graves' disease and Evans' syndrome had not occurred previously in her f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Insufficient suppressor T-cell activity and anti-TSH receptor autoantibodies, such as oligoclonal immunoglobulin G2 antibodies, are listed as potential pathogenetic factors. 73 Furthermore, Yasuda et al 74 suggested that autoimmune hemolytic anemia might be an effect of the stimulation of the activated reticuloendothelial phagocytic system by thyroid hormones. Recently, a case of Evans syndrome in the course of secondary hyperthyroidism caused by pituitary TSH--secreting adenoma has been described.…”
Section: Autoimmune Hemolytic Anemia and Evans Syndromementioning
confidence: 99%
“…Insufficient suppressor T-cell activity and anti-TSH receptor autoantibodies, such as oligoclonal immunoglobulin G2 antibodies, are listed as potential pathogenetic factors. 73 Furthermore, Yasuda et al 74 suggested that autoimmune hemolytic anemia might be an effect of the stimulation of the activated reticuloendothelial phagocytic system by thyroid hormones. Recently, a case of Evans syndrome in the course of secondary hyperthyroidism caused by pituitary TSH--secreting adenoma has been described.…”
Section: Autoimmune Hemolytic Anemia and Evans Syndromementioning
confidence: 99%
“…A genetic predisposition to both Graves' disease and AITP was highlighted by Bizzarro [26] who found these two disorders in three female relatives, all of whom were positive for HLA-B8 and DR3 phenotypes. Graves' disease or Hashimoto thyroiditis and AITP have also been reported in association with other autoimmune disorders such as myasthenia gravis [18,21,30], Guillain-Barre syndrome [29], insulindependent diabetes mellitus [19], celiac disease [37], and Evans' syndrome (a condition characterized autoimmune hemolytic anemia and AITP) [20,24,25,28]. On the other hand, some investigators have analyzed the prevalence of thyroid disorders in patients with AITP.…”
Section: Introductionmentioning
confidence: 99%
“…Graves' disease (GD) is caused by autoimmune nature, and is sometimesaccompaniedwith other autoimmunediseases, such as typel diabetes mellitus (1), myasthenia gravis (2-4), Sjogren's syndrome (5,6), and immune thrombocytopenic purpura (7)(8)(9)(10)(11)(12). Whereas a few reports describe the association of GD with polymyositis (PM) (2,3,(13)(14)(15), dermatomyositis (DM) (16,17), and scleroderma (13,(18)(19)(20)(21) in the English-language literature, there is only one case report describing a patient with GDcomplicated with PMand scleroderma (13).…”
Section: Introductionmentioning
confidence: 99%